PENGARUH PENERAPAN MODEL PEMBELAJARAN VARK(VISUAL, AURAL, READ/WRITE & KINESTHETIC) BERBANTUAN LKS UNTUK MENINGKATKAN HASIL BELAJAR TIK KELAS XI DI SMA NEGERI 3 SINGARAJA TAHUN AJARAN 2013/2014 - I Gusti Ayu Agung Riesa M; Dessy Seri Wahyuni; I Gede Mahendra Darmawiguna (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The purpose of this study and was for determine (1) the influence of the application of learning models VARK of ICTclassroom learning outcomes XI SMA Negeri 3 Singaraja, (2) student responde toward the application of learning models VARK.This type of research is a quasi-experimental with posttest study design-Only Control Group Design. The population of this study were the entire class XI SMA Negeri 3 Singaraja academic year 2013/2014. The samples of this study were 53 students which were taken from XI IPA3I and XI IPA4. XI IPA3 class was used as an experimental class and XI IPA4 was used as the control class. There are two types of variables in this study, are (1) the independent variable whice is VARK learning model, and (2) the dependent variable hicw is the students’ learning outcomes. The data was collected by using a multiple-choice test method for measuring the cognitive. The data was then analyzed by studying the results of test requirements that include tests of normality, homogeneity test and t-test for the responses were analyzed by using the questionnaire method.Based on the analysis of data obtained, the normality and homogeneity test of both two groups distributed normal and homogeny. There is a significant effect for learning outcomes among students who were taught by using learning model of VARK. This indicated that the learning outcomes of students with learning models VARK is higher than direct konvensional model. Obtained positively to the application of learning models VARK.